PROBLEM AND METHODOLOGICAL SOLUTION FOR CALCULATIONS ALTOGETHER PRODUCTIVITY IN AGRICULTURE - M. Drobac, Milorad (Economics of Agriculture, 2007)
Author is engaged with problems of incorporating intermediate inputs in productivity measurements in agriculture, i.e. including intermediate inputs in a function of attached value because in that way its more comprehensively showing structure of agriculture production. The importance of use of superlative indexes that display qualitative changes in measurement of partial productivity is short analyzed. Its overlooked the influence of technical-technological progress on altogether productivity adequately measure the importance in growth of production. Its obverse that the problems of productivity measurement in agriculture are more complex than in other sectors of production. Main cause of that condition is, beside other, acceptation and use of different models and procedures at determination of productivity parameters.